Patient survival after resection of skeletal metastases and endoprosthetic reconstruction - Merčun, Aljaž (Radiology and oncology (Ljubljana), 2025)
Background: The aim of this nation-wide 2009-2021 cohort study was to analyze postoperative survival of patients with resected appendicular skeletal metastases and endoprosthetic reconstruction in comparison to sarcoma patients and non-oncological reconstructions. Patients and methods: A single institution nation-wide cohort of 144 consecutive patients with tumor endoprosthetic reconstructions (32 resected metastases, 73 resected sarcomas, 39 non-oncological) were stratified into histopathological groups according to the 2013-SPRING prediction model. Their survival was analyzed with the Kaplan-Meier method and Cox regression. Results: The observed patient survival rates after wide resection of fast/moderate/slow growing metastases were 25/55/88% at 2 years and 10/30/83% at 5 years, while in sarcomas the observed survival rates were 80% at 2 years and 69% at 5 years. Estimated mean postoperative survival after resection of skeletal metastases was significantly shorter in comparison to sarcomas (4.6 years vs. 9.1 years, log-rank p 1 metastasis, diagnostic group fast-growing metastases and higher preoperative C-reactive protein (CRP). Conclusions: Wide resection and endoprosthetic reconstruction offer a reliable solution in selected patients with skeletal metastases. Higher age, fast-growing metastases (from bladder cancer, colorectal, hepatocellular, lung cancer, malignant melanoma, unknown origin), pathologic fracture or >1 metastasis and elevated CRP predict shorter patient survival and may represent a relative contraindication in this regard.
Keywords: endoprosthetic reconstruction; patient survival; skeletal metastases; wide resection